From State to Market: A Survey of Empirical Studies on Privatization - William L. Megginson; Jeffry M. Netter (Fondazione Eni Enrico Mattei (FEEM), 1999)
This study surveys the academic and professional literature examining the privatisation of state-owned enterprises (SOEs), with a focus on empirical studies. Privatisation has been instrumental in reducing state ownership in many countries and had a transforming effect on global stock markets, although the role of SOEs in many other countries is similar to what it was two decades ago. Countries have adopted large-scale privatisation programs primarily for two reasons: first, the conclusive evidence that privately-owned firms outperform SOEs and, second, the empirical evidence clearly shows that privatisation significantly (often dramatically) improves the operating and financial performance of divested firms. Governments can also raise significant revenues by selling SOEs. While the choice between privatisation via public share offering versus through asset sales is still imperfectly understood, factors such as firm size, government fiscal condition, and the state of national economic development are important influences. Further, those countries which have chosen the mass (voucher) privatisation route have done so largely out of necessity–and face ongoing efficiency problems as a result. Governments have great discretion in pricing the SOEs they sell, especially those being sold via public share offering, and they use this discretion to pursue political and economic ends. Finally, investors who purchase the shares of firms being privatised earn significantly positive excess returns both in the short-run (due to deliberate underpricing of share issues by the government) and over one, three, and five-year investment horizons.
Keywords: E22; E24; G32; G24; H27; L32; L33; 330; Capital; Investment; Employment; Financing policy; Ownership structure; Investment banking; Venture capital; Brokerage; Public economics; Sources of revenue; Public enterprises; Boundaries of public and private enterprise; Privatisation; Contracting out; Privatisierung; Ökonometrie; Welt